Pengaruh Kepemimpinan Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Cipta Mandiri Perkasa Karawang - Ilham Abdurrohman; Asep Jamaludin; Nandang Nandang (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to determine, analyze, explain the correlation and partial or simultaneous influence between Leadership and Work Environment on Employee Performance at PT. Cipta Mandiri Perkasa Karawang. This type of research is quantitative research with verification research methods. Sample at PT. Cipta Mandiri Perkasa Karawang taken by 60 respondents. The sampling technique in this research used a saturated sample technique (Non-probability sampling). The analysis tool used in this research uses SPSS 26 for MacOs software. The analysis model in this research uses a path analysis model. The research results show that there is a correlation between the independent and dependent variables of 0.861 in the Very strong category. The partial influence of leadership on employee performance at PT. Cipta Mandiri Perkasa Karawang by 40.5%. Meanwhile, the partial influence of the work environment on employee performance at PT. Cipta Mandiri Perkasa Karawang amounted to 37.7%. The simultaneous influence of leadership and work environment on employee performance is 78.2%. The influence of other variables outside the model is 21.8%. Keywords: Leadership, Work Environment, Employee Performance